Speech recall and word recognition depending on prosodic and musical cues as well as voice pitch - Rozanovskaya, Anna; Sokolova, Taisia (2011)
Within this study, speech perception in different conditions was examined. The aim of the research was to compare perception results based on stimuli mode (plain spoken, rhythmic spoken or rhythmic sung stimuli) and pitch (normal, lower and higher). In the study, an experiment was conducted on 44 participants who had been asked to listen to 9 recorded sentences in Russian language (unknown to them) and write them down using Latin letters. These 9 sentences were specially prepared using different phonetic environments, voice pitches, rhythmic structures and presentation modes (sung/spoken). The analysis showed that recall ability (for both the amount of remembered and recall accuracy) had been affected by the mode of stimuli: sung stimuli had been remembered better than spoken ones, even compared to the rhythmical spoken condition. Segmentation accuracy turned out to be enhanced only with introduction of rhythm, without any significant improvement for the sung stimuli. Voice height was found to influence perception of the phonetic image, affecting recognition of vowels in stressed positions and consonants both in stressed and unstressed positions. This effect was especially strong for the higher pitch and plain spoken stimuli. The data obtained in the study and experimental design developed for it may be used both for further research purposes and for creating educational settings.